2015
DOI: 10.1038/nrmicro.2015.6
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcus: from environmental saprophyte to global pathogen

Abstract: Cryptococcosis is a globally distributed invasive fungal infection that is caused by species within the genus Cryptococcus which presents substantial therapeutic challenges. Although natural human-to-human transmission has never been observed, recent work has identified multiple virulence mechanisms that enable cryptococci to infect, disseminate within and ultimately kill their human host. In this Review, we describe these recent discoveries that illustrate the intricacy of host-pathogen interactions and revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
392
0
26

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 445 publications
(419 citation statements)
references
References 137 publications
(130 reference statements)
1
392
0
26
Order By: Relevance
“…61 CNS penetration by Cryptococcus spp occurs via a transcytosis, paracellular, and the Trojan horse pathways. 6,62 Post-mortem neuropathological examinations of patients' brains have demonstrated that C. neoformans' main virulence factor, its polysaccharide capsule which is extensively released during infection, is ingested and localizes inside of microglia. 63,64 In the periphery, the capsular polysaccharide can interfere with phagocytosis, antigen presentation, leukocyte migration and proliferation, and specific antibody responses, and can enhance HIV replication.…”
Section: Opportunistic Fungal Infectionsmentioning
confidence: 99%
“…61 CNS penetration by Cryptococcus spp occurs via a transcytosis, paracellular, and the Trojan horse pathways. 6,62 Post-mortem neuropathological examinations of patients' brains have demonstrated that C. neoformans' main virulence factor, its polysaccharide capsule which is extensively released during infection, is ingested and localizes inside of microglia. 63,64 In the periphery, the capsular polysaccharide can interfere with phagocytosis, antigen presentation, leukocyte migration and proliferation, and specific antibody responses, and can enhance HIV replication.…”
Section: Opportunistic Fungal Infectionsmentioning
confidence: 99%
“…En México, C. neoformans se ha aislado en el 20.7% de las muestras de excrementos de palomas colectados en áreas urbanas, y en menor proporción en verduras, frutas y excrementos de otras aves 10 . La presentación clínica más común es pulmonar, de donde puede diseminarse por vía hematógena al SNC y causar meningoencefalitis [11][12][13] . Al viajar por el torrente sanguíneo, el hongo inhibe la respuesta inmunitaria del huésped y la producción de factor de necrosis tumoral, entre otros 14,15 .…”
Section: Discussionunclassified
“…Evidence of latency exists in the finding of continuous antibody production, [11][12][13][14] molecular studies indicating that cryptococcosis presenting in Africans living in Europe was acquired many years earlier, 15,16 and in autopsy studies from patients without a history of cryptococcal disease or exposure describing pulmonary granulomas containing C. neoformans. 17,18 The ability of the fungus to persist in humans without triggering a successful immune reaction has likely evolved due to its saprophytic nature (reviewed in [7][8][9] ). For example, C. neoformans is able to survive and replicate within macrophages in a similar way to which it exists as an intracellular parasite of amoebae in the environment.…”
Section: Pathophysiologymentioning
confidence: 99%